Clinical Potential of Effective Noninvasive Exclusion of KEL1-Positive Fetuses in KEL1-Negative Pregnant Women - Böhmová, Jana; Vodička, Radek; Ľubušký, Marek; Holusková, Iva; Studničková, Martina; Kratochvílová, Romana; Krejčiříková, Eva; Janíková, Mária; Durdová, Veronika; Dolezalová, Tereza; Filipová, Hana; Dušek, Ladislav; et al. (Fetal diagnosis and therapy, 2016)
BACKGROUND: The clinical importance of assessing the fetal KEL genotype is to exclude 'K'-positive fetuses (genotype KEL1/KEL2) in 'K'-alloimmunized pregnant women (genotype KEL2/KEL2). Noninvasive assessment of the fetal KEL genotype is not yet available in the Czech Republic. OBJECTIVE: The aim of this study was to assess the fetal KEL1/KEL2 genotype from cell-free fetal DNA in the plasma of KEL2/KEL2 pregnant women. METHODS: The fetal genotype was assessed by minisequencing (a dilution series including control samples). A total of 138 pregnant women (between the 8th and 23rd gestational week) were tested by minisequencing. The fetal genotype was further verified by analysis of a buccal swab from the newborn. RESULTS: Minisequencing proved to be a reliable method. In 2.2% (3/138) of the examined women, plasma sample testing failed; 94.8% (128/135) had the KEL2/KEL2 genotype, and a total of 3.1% of fetuses (4/128) had the KEL1/KEL2 genotype. Sensitivity and specificity reached 100% (p < 0.0001). CONCLUSION: Minisequencing is a reliable method for the assessment of the fetal KEL1 allele from the plasma of KEL2/KEL2 pregnant women.
Keywords: genotypizační techniky; Pregnancy; membránové glykoproteiny; těhotenství; False Negative Reactions; Adult; antigeny krevních skupin; dospělí; Blood Group Antigens; Fetus; Erythroblastosis, Fetal; falešně pozitivní reakce; plod; falešně negativní reakce; lidé; ženské pohlaví; Humans; Metalloendopeptidases; Membrane Glycoproteins; Sensitivity and Specificity; senzitivita a specificita; Female; Genotyping Techniques; metaloendopeptidasy; False Positive Reactions; hemolytická nemoc plodu a novorozence